College algebra and trigonometry - Lial, Margaret L.; Hornsby, E. John; Schneider, David I.; Daniels, Callie J. (Pearson Education Limited, 2017)
'College Algebra and Trigonometry' engages and supports students in the learning process by developing both the conceptual understanding and the analytical skills necessary for success in mathematics.